Suicidal attempts and ideations in Kenyan adults with psychotic disorders: An observational study of frequency and associated risk factors - Ongeri, Linnet; Kariuki, Symon M.; Nyawira, Miriam; Schubart, Chris; Tijdink, Joeri K.; Newton, Charles R. J. C.; Penninx, Brenda W. J. H. (Frontiers in Psychiatry, 2023)
Background: Psychotic disorders increase the risk for premature mortality with up to 40% of this mortality attributable to suicide. Although suicidal ideation (SI) and suicidal behavior (SB) is high in persons with psychotic disorders in sub-Saharan Africa, there is limited data on the risk of suicide and associated factors among persons with psychotic disorders. Methods: We assessed SI and SB in persons with psychotic disorders, drawn from a large case-control study examining genetics of psychotic disorders in a Kenyan population. Participants with psychotic disorders were identified using clinical review of records and diagnosis confirmed with Mini International Neuropsychiatric interview (MINI). We conducted bivariate and multivariable logistic (for binary suicide outcomes) or linear regression (for suicide risk score) analysis for each of the suicide variables. Results: Out of 619 participants any current SI or lifetime suicidal attempt was reported by 203 (32.8%) participants with psychotic disorders, of which 181 (29.2%) had a lifetime suicidal attempt, 60 (9.7%) had SI in the past month, and 38 (20.9%) had both. Family history of suicidality was significantly associated with an increased risk of suicidality across all four outcomes: SI (OR=2.56(95% CI: 1.34-4.88)), suicidal attempt (OR=2.01(95% CI: 1.31-3.06)), SI and SB (OR=2.00(95% CI: 1.31-3.04)) and suicide risk score (beta coefficient (β)=7.04 (2.72;11.36), p=0.001)). Compared to persons aged <25 years, there was reduced odds for SI for persons aged ≥25 years (OR=0.30(95% CI: 0.14-0.62)), and ≥45 years (OR=0.32 (95% CI: 0.12-0.89)). The number of negative life events experienced increased the risk of SI and SB (OR=2.91 (95% CI: 1.43-5.94)) for 4 or more life events. Higher negative symptoms were associated with more suicidal attempts (OR=2.02(95%CI: 1.15-3.54)). Unemployment was also associated with an increased risk for suicidal attempts (OR=1.58(95%CI: 1.08-2.33) and SI&SB (OR=1.68(95% CI: 1.15-2.46)), Conclusion: SI&SB is common in persons with psychotic disorders in this African setting and is associated with sociodemographic factors such as young age and unemployment, and clinical factors such as family history of suicidality. Interventions targeted at the community (e.g., economic empowerment) or at increasing access to care and treatment for persons with psychotic disorders may reduce this risk of suicide.